2005
DOI: 10.1159/000084589
|View full text |Cite
|
Sign up to set email alerts
|

Body Temperature – A Marker of Infarct Size in the Era of Early Reperfusion

Abstract: We measured body temperature in 40 consecutive patients treated for a first ST elevation acute myocardial infarction (AMI) with primary percutaneous coronary interventions. Left ventricular function was assessed by echocardiography, and blood samples were drawn for highly sensitive C-reactive protein (hs-CRP), white blood cell (WBC) count, fibrinogen, creatine kinase (CK), and cardiac troponin I levels (cTnI). The median (25th, 75th quartiles) peak 24-hour temperature was 37.4°C (36.9°C, 37.6°C). Variables sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
0
15
1
Order By: Relevance
“…Elevated heart rate, respiratory rate, and leukocytosis are all reported independent risk factors for mortality (25)(26)(27)(28)(29). Elevated heart rate, respiratory rate, and leukocytosis are all reported independent risk factors for mortality (25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated heart rate, respiratory rate, and leukocytosis are all reported independent risk factors for mortality (25)(26)(27)(28)(29). Elevated heart rate, respiratory rate, and leukocytosis are all reported independent risk factors for mortality (25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated heart rate, respiratory rate, and leukocytosis are all reported independent risk factors for mortality (25)(26)(27)(28)(29). A small series of 40 patients reported a positive correlation with infarct size, whereas a previous CARDINAL analysis has reported statistically nonsignificant negative association between body temperature and infarct size (28,29). The relationship between body temperature and infarct size remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, it can often be a clinical challenge to determine whether the fever is due to the MI, to a complicating infection, or to other causes of systemic inflammation. Regardless of the etiology, because fever has a strong influence on oxygen consumption, it is important to recognize preventable or treatable underlying causes of fever that might predispose a patient to infarct extension and greater infarct size (19,20). …”
Section: Discussionmentioning
confidence: 99%
“…They concluded that inappropriate vasodilation in patients with systemic inflammatory response syndrome may play an important role in the pathogenesis and persistence of shock, with or without infection (22). While Ben-Dor and colleagues found that fever was frequent after reperfusion, they concluded that it was due to infarct size and not to a nonspecific systemic inflammatory response (19). In their study, fever was correlated with high-sensitivity C-reactive protein but not with fibrinogen levels or white blood cell count.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between the extent of necrosis and the rise in temperature has been shown. 60,61 Animal studies indicate that elevated corporal temperature might be harmful prior to and directly after an acute coronary syndrome or myocardial infarction. 62 Fever after myocardial tissue loss occurs due to ischemic cell death, resulting in the production of cytokines.…”
Section: Ischemic Diseasesmentioning
confidence: 99%